Beyond fluorodeoxyglucose: Molecular imaging of cancer in precision medicine - Malik E. Juweid; Soud F. Al‐Qasem; Fadlo R. Khuri; Andrea Gallamini; Philipp Lohmann; Hans‐Joachim Ziellenbach; Felix M. Mottaghy (CA: A Cancer Journal for Clinicians, 2025)
Abstract Cancer molecular imaging is the noninvasive visualization of a process unique to or altered in neoplasia, such as proliferation, glucose metabolism, and receptor expression, which is relevant to patient management. Several molecular imaging modalities are now available, including magnetic resonance, optical, and nuclear imaging. Nuclear imaging, particularly using fluorine‐18–fluorodeoxyglucose positron emission tomography, is widely used in the staging and response assessment of multiple cancer types. However, at this writing, new nuclear medicine probes, especially positron emission tomography tracers, are increasingly used or are being investigated for cancer evaluation. This review focuses on these probes, their biologic targets, and the applications or potential applications for their use in the assessment of various neoplasms, including both probes available for commercial use—such as somatostatin receptor ligands in neuroendocrine tumors, prostate‐specific membrane antigen ligands in prostate cancer, norepinephrine analogs in neural crest tumors like neuroblastoma, and estrogen analogs in breast cancer—and others in clinical development, such as fibroblast‐activating protein inhibitors, C‐X‐C chemokine receptor type 4 ligands, and monoclonal antibodies targeting receptor tyrosine kinases, CD4‐positive or CD8‐positive tumor‐infiltrating lymphocytes, tumor‐associated macrophages, and cancer stem cell biomarkers. These developments represent a major step toward the integration of molecular imaging as a powerful tool in precision medicine, with an expectedly significant impact on patient management and outcome.